1989
DOI: 10.1007/bf02327261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elemental sulphur on chemical changes and nutrient availability in calcareous soils

Abstract: Elemental sulphur was added to three calcareous soils varying in texture, CaCO 3 content, native phosphorus and micronutrient content at a rate of 0.5, 1.5 and 3.0% (w/w). The experiment was carried in soil columns which were intermittentantly leached and incubated at 30~ for 3,6,9, and 18 weeks. Sulphur applied at a rate of 0.5% significantly decreased the pH and increased the EC and the soluble sulphate content in all three soils and their leachates with slight differences among soils. Sulphur application ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 10 publications
4
29
1
Order By: Relevance
“…Table 8 results was obtained by [79] who found that it may be due to that sulphur reduced pH of the soil and making phosphorus and micronutrients more available to the plant. Our results were also supported by [80] who reported that utilization of sulfur in calcareous soil and with neutralizing lime improved accessibility of iron. [79] showed the same results.…”
Section: Plant P Uptakesupporting
confidence: 88%
See 1 more Smart Citation
“…Table 8 results was obtained by [79] who found that it may be due to that sulphur reduced pH of the soil and making phosphorus and micronutrients more available to the plant. Our results were also supported by [80] who reported that utilization of sulfur in calcareous soil and with neutralizing lime improved accessibility of iron. [79] showed the same results.…”
Section: Plant P Uptakesupporting
confidence: 88%
“…The comparable results was obtained by [14] who found that it may be due to that sulphur reduced pH of the soil and making phosphorus and micronutrients more available. Similarly [79] and [80] and [81] found that sulphur has helpful outcome from the soil on releasing phosphorus and increased the yield of plant. Comparable results were also reported by [41] who found that concentration of P might be amplified when organic materials are mixed with rock phosphate.…”
Section: Post Harvest Soil P Contentmentioning
confidence: 99%
“…It is reported that oxidizing each mole of S produces two moles of hydrogen ions (H + ) in the soil and reduces soil pH that leads to dissolution of nutrients in the root zone (Modaihsh et al 1989;Kaplan and Orman, 1998;Iqbal et al 2012). Different studies have been reported on micronutrient biofortification in plants under normal soils (Hussain et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Schnug and Finck (16) showed that high doses of acidifying N fertilizers did not improve the uptake of micronutrients by celery grown on a calcareous soil. Reported effects of S applications on micronutrient availability are also inconsistent, varying form clearly positive (6,12,13) to hardly any response (7,8).…”
mentioning
confidence: 94%